Cover Picture: Advanced techniques for gene heterogeneity research: Single‐cell sequencing and on‐chip gene analysis systems (View 1/2022). Issue 1 (31st January 2022) - Dong, Zaizai; Wang, Yu; Yin, Dedong; Hang, Xinxin; Pu, Lei; Zhang, Jianfu; Geng, Jia; Chang, Lingqian
Abstract : In article number 20210011, Lingqian Chang, Jia Geng and their co‐wokers have shown panorama of recent advances in single‐cell sequencing techniques and on‐chip single‐cell gene analysis systems.